Epistemic Beliefs and Learners' Self-Efficacy as Predictors of Language Learning Strategies: Toward Testing a Model - Shirzad, Shaghayegh; Barjesteh, Hamed; Dehqan, Mahmood; Zare, Mahboubeh (Frontiers in Psychology, 2022)
Understanding the beliefs held by the learners about learning a language, and the way they utilize their thought about knowledge and learning seem to be essential for planning a constructive language program. Following this line of research, this paper aims at testing a hypothetical model of linking facts of epistemic beliefs (EBs) to learners’ self-efficacy (LSE) through mediating effects of subscales of language learning strategies (LLSs). To this end, a sample of 300 Iranian high school students taking regular courses completed three survey questionnaires. At this stage, correlational analysis and structural equation modeling (SEM) was employed to probe the causal interconnections, analyze the model, and outline the conceptual framework. The results revealed that LSE framework can adequately account for learners’ LLSs. In particular, the results indicated that efforts, persistence, and imitation positively and significantly influenced LLSs. However, EBs was known to be a significant factor in demoting LLSs. Notably, knowledge and learning agent were the negative predictors of LLSs. This paper suggests that LSE has higher explanatory power than EBs in predicting LLSs. The findings can encourage second language (L2) teachers and materials developers to apply LSE strategies to promote academic achievement.